2021
DOI: 10.1016/j.scitotenv.2020.142283
|View full text |Cite
|
Sign up to set email alerts
|

Multi O- and S-isotopes as tracers of black crusts formation under volcanic and non-volcanic atmospheric conditions in Sicily (Italy)

Abstract: isotopes as tracers of black crusts formation under volcanic and non-volcanic atmospheric conditions in Sicily (Italy),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 121 publications
(169 reference statements)
1
16
0
Order By: Relevance
“…According to the morphological results, there are a large number of idiomorphic gypsum crystals on the crusts, with bigger size than PM 10 and PM 2.5 . Therefore, it is probable that the gypsum is not from the deposition of atmospheric sulphate but rather from reaction between the carbonate and sulfur compounds, which is consistent with isotopic data (Genot et al, 2020;Aroskay et al, 2021).…”
Section: Black Crust Forming Mechanism Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…According to the morphological results, there are a large number of idiomorphic gypsum crystals on the crusts, with bigger size than PM 10 and PM 2.5 . Therefore, it is probable that the gypsum is not from the deposition of atmospheric sulphate but rather from reaction between the carbonate and sulfur compounds, which is consistent with isotopic data (Genot et al, 2020;Aroskay et al, 2021).…”
Section: Black Crust Forming Mechanism Discussionsupporting
confidence: 73%
“…As a result, frequent sulphation process occurs on the marble surface in this period, demonstrated in Figure 9. SiO 2 oxidation by O 2 with metal ion catalysts also contributes to the sulphation (Aroskay et al, 2021), since Al, Mn, Fe, Ni, Cu, Zn, et al can be detected in the rainwater (Vlastos et al, 2019) and crusts.…”
Section: Black Crust Forming Mechanism Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the possible production of S-MIF in sulfur recombination reactions that may occur in gaseous thermochemical reactions such as combustion and volcanism, it is further argued that similar processes may occur in Archean, providing additional non-photochemical S-MIF processes that may need to be considered in interpreting Archean data. , This idea was preliminarily tested by physical chemistry experiments and atmospheric chemistry models . Subsequent multiple sulfur isotope measurements of modern sulfate aerosols however found that Δ 33 S anomalies are also correlated with mineral dusts. It was preliminarily proposed that heterogeneous sulfur reactions account for such Δ 33 S anomalies, but Δ 33 S signs among different follow-up studies are different. A deep mechanistic understanding on the possible chemical reaction that may lead to Δ 33 S anomalies is useful for using Δ 33 S to identify and quantify any missing sulfate formation pathway in the modern atmosphere with profound implications for air pollution and climate change. …”
Section: Introductionmentioning
confidence: 99%
“…Among the identified alteration and degradation products, sulphates predominate, specifically gypsum and syngenite. The authigenic precipitation of gypsum on carbonate stone is due to the chemical reaction between sulphate (SO 4 2- ) and calcite (CaCO 3 ), with various possible origins of the sulphate anion from anthropogenic sources, marine aerosols, and also by volcanic emissions since the Etna volcano is only about 50 km from Lentini (Aroskay et al 2021 and references therein). On the other hand, syngenite originates on calcareous substrate through the hydrolytic mobilisation of alkaline metals from volcanic glass in the presence of percolating solutions enriched in sulphate anions.…”
Section: Discussionmentioning
confidence: 99%